Pengaruh Pemberian Pupuk Kandang dan Pupuk Organik Cair Terhadap Pertumbuhan dan Hasil Kentang (Solanum tuberosum L.) Kultivar Granola - Endang Kantikowati; Karya Karya; Latip Permana (Paspalum: Jurnal Ilmiah Pertanian, 2023)
Potato (Solanum tuberosum L.) is one of the staple foods in the world. Potato productivity must be increased to comply public consumption. This study aims to determine the interaction effect of doses of chicken manure and concentration of liquid organic fertilizer on the growth and yield of potato cultivar Granola. The research was conducted from February to June 2021, in Cikole Village, Margamulya Village, Bandung Regency, West Java Province with an altitude of 1,200 m above sea level and included in the C2 agro-climatological zone based on Oldeman's classification. The experiment used a factorial randomized block design (RBD). The first factor was the dose of manure, which consisted of 3 treatment levels, namely 0, 10 and 20 tons/ha. The second factor was the concentration of liquid organic fertilizer, which consisted of 3 treatment levels, namely: 0, 2, and 4 mL/L. Each treatment was replicated 3 times. The results showed that the interaction effect between doses of manure and liquid organic fertilizer occurred on plant height at 28 days after sowing and number of tubers per plant. The single effect of manure doses or liquid organic fertilizer concentration has made a difference in the growth and yield components. A dose of 10 tons/ha of manure or a concentration of 4 mL/L of liquid organic fertilizer could increase potato yields, compared to without manure or liquid organic fertilizer.